Analysis of the Independent Curriculum (Independent Learning, Independent Transformation, and Independent Sharing) - Zainudin, Agus; Hepni, Hepni; Nawangsari, Dyah; Ubaidillah, Ubaidillah (UAS PRESS, 2025)
The Merdeka Belajar policy, introduced by the Minister of Education and Culture, Nadiem Makarim, aims to improve the quality of education in Indonesia by granting teachers and students the freedom to manage the learning process. The Merdeka Curriculum, as part of this policy, offers flexibility in teaching methods oriented toward holistic student character development, including academic competence, soft skills, and critical thinking abilities. The implementation of the Merdeka Curriculum is carried out through three approaches: Mandiri Belajar (Independent Learning), Mandiri Berubah (Independent Transformation), and Mandiri Berbagi (Independent Sharing), each providing varying degrees of autonomy for schools to adapt learning processes to local needs. This study employs a qualitative method with a literature review to analyze the implementation of the Merdeka Curriculum, covering literacy, numeracy, character surveys, and project-based learning aligned with the Pancasila Student Profile. The results indicate that the Merdeka Curriculum offers opportunities for teachers to create innovative and relevant learning experiences, although it requires support in training and collaboration among stakeholders to achieve optimal outcomes. With this approach, it is expected that Indonesian education can accommodate students' needs in an era of globalization and technological transformation.